(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The current research aims to identify the attitudes of a sample of mathematics teachers in the city of Lattakia towards the use of technical mathematics labs in the primary education stage, To achieve the research objectives, the researcher applied the descriptive approach and designed an attitude questionnaire to measure the attitudes of mathematics teachers. The questionnaire consisted of (20) statements and was distributed to (123) mathematics teachers in the primary education stage in the city of Lattakia.After distributing the questionnaire and transcribing the answers, the research yielded a set of results represented by the presence of positive attitudes among mathematics teachers towards the use of the technical mathematics laboratory in the basic education stage, as well as the presence of a statistically significant difference in attitudes. Mathematics teachers’ towards using the technical mathematics lab, which the researcher attributed to the variable of training courses on the use of educational tools, in favor of those who followed one or more courses. The results of the study also showed that there was no statistically significant difference in the attitudes of mathematics teachers towards using the technical mathematics lab according to the variable of academic and educational qualifications